Pertanggung Jawaban Hukum Pihak Ekspedisi Pengiriman Terhadap Barang Hilang atau Rusak - Prasetyo, Edy; Budiono, Arief; Sybelle, Jan Alizea (Jurnal Penegakan Hukum dan Keadilan, 2024)
There are no clear provisions in the regulations that regulate the extent to which the delivery service is responsible for losses suffered by consumers for goods sent that are damaged or lost and the uncertainty of the obligations and fines imposed by the delivery service when it does not fulfill the promise of timely delivery becomes separate problem for consumers. This study aims to determine the accountability and efforts that can be made by consumers in the case of lost or damaged goods at PT. Tri Adi Together (Anteraja). This research is a normative juridical research using deductive thinking method. Data collection techniques were carried out by interviewing and library documents. This study uses a qualitative approach in analyzing the data that has been obtained: The results show (1) there are two forms of responsibility that have been carried out by PT. Tri Adi Bersama (Anteraja) in the case of lost or damaged goods, namely providing compensation to the owner of the goods and being responsible for unlawful acts committed by its employees. (2) There are efforts that can be made by consumers to demand the responsibility of PT. Tri Adi Bersama (Anteraja) for objects sent in the event of a loss, including efforts to pass the Consumer Dispute Settlement Agency (BPSK) with arbitration, conciliation and mediation as efforts made outside of court as well as filing lawsuits, examinations and verification as efforts through legal channels.